Hypermagnesemia in Clinical Practice - Aya Hasan Aal-Hamad; Abdullah M. Al-Alawi; Masoud Salim Kashoub; Henrik Falhammar (Medicina, 2023)
Hypermagnesemia is a relatively uncommon but potentially life-threatening electrolyte disturbance characterized by elevated magnesium concentrations in the blood. Magnesium is a crucial mineral involved in various physiological functions, such as neuromuscular conduction, cardiac excitability, vasomotor tone, insulin metabolism, and muscular contraction. Hypomagnesemia is a prevalent electrolyte disturbance that can lead to several neuromuscular, cardiac, or nervous system disorders. Hypermagnesemia has been associated with adverse clinical outcomes, particularly in hospitalized patients. Prompt identification and management of hypermagnesemia are crucial to prevent complications, such as respiratory and cardiovascular negative outcomes, neuromuscular dysfunction, and coma. Preventing hypermagnesemia is crucial, particularly in high-risk populations, such as patients with impaired renal function or those receiving magnesium-containing medications or supplements. Clinical management of hypermagnesemia involves discontinuing magnesium-containing therapies, intravenous fluid therapy, or dialysis in severe cases. Furthermore, healthcare providers should monitor serum magnesium concentration in patients at risk of hypermagnesemia and promptly intervene if the concentration exceeds the normal range.